Lost in transition: Patient-identified barriers to adult urological spina bifida care. Issue 6 (December 2018) - Hettel, Daniel; Tran, Christine; Szymanski, Konrad; Misseri, Rosalia; Wood, Hadley
Summary: Introduction: It has been established that patients with congenital diseases, including spina bifida (SB) are often lost to routine medical care in young adulthood. While the reasons for this observation are not entirely defined, many believe it is multifactorial. Objective: This study sought to characterize self-reported barriers to transition among adults with SB who failed to transition to adult urological care. Study design: This study, conducted at two tertiary centers with established adult myelomeningocele multidisciplinary clinics, enrolled patients with SB who had not been seen in >18 months. A visit was scheduled and upon arrival patients were provided a questionnaire with 22 yes/no questions about barriers to arranging a visit and eight questions regarding their health issues. Questions were categorized as relating to patient factors, provider factors, and system factors. To facilitate targeted areas of improvement, patient factors were further subdivided into self-management/support (SMS), preferences, and education, and provider factors into knowledge, communication, and location. System factors included only questions related to insurance issues. The questionnaire was uncomplicated, which eliminated the need for assistance when answering the questions. Results: There were 27 questionnaires collected. Overall, a total of seven patients (26%) identified no barriers to follow-up, eight identified one barrier (30%), and 12 (44%) identified more than one barrier. Patient factors made up approximately 52% (28 of 54 total "Yes" responses) of all barriers, with Preference being the largest contributor (30%, 16/54) (Fig.). Provider factors accounted for about 37% (20/54) of all barriers, with the Communication (26%, 14/54) subcategory making up the vast majority. System factors contributed only 11% (6/54) of all barriers. The majority of patients (18/27, 67%) reported having a new health issue since their last visit to their pediatric urologist, with only five of 18 (28%) seeking urological care. Discussion: This study demonstrated that the decision to pursue adult urologic care is multifactorial. The questionnaire may not have captured all of the reasons SB patients are lost to follow-up, as a quarter of patients did not identify a barrier. Limitations of this study include the small number of participants, use of only two study locations, and the closed-ended nature of the questionnaire. Conclusion: Multiple factors contribute to the SB patient's decision to pursue adult urologic care. Targeted areas of improvement include provider communication at both the pediatric and adult level, as well as education regarding patient preferences and SMS. Figure Overall proportion of barriers to establishing follow-up among adults with spina bifida. SMS = self-management/support.